2001
DOI: 10.1073/pnas.191211198
|View full text |Cite|
|
Sign up to set email alerts
|

Polymorphism in glutathione S -transferase P1 is associated with susceptibility to chemotherapy-induced leukemia

Abstract: Glutathione S -transferases (GSTs) detoxify potentially mutagenic and toxic DNA-reactive electrophiles, including metabolites of several chemotherapeutic agents, some of which are suspected human carcinogens. Functional polymorphisms exist in at least three genes that encode GSTs, including GSTM1, GSTT1, and GSTP1. We hypothesize, therefore, that polymorphisms in genes that encode GSTs alter susceptibility to chemotherapy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
139
1
2

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 236 publications
(148 citation statements)
references
References 52 publications
6
139
1
2
Order By: Relevance
“…were related to secondary leukemia. 13,27 Also, the presence of germ line mutations such as those of p53 (Li-Fraumeni syndrome) may underlie the occurrence of primary cancers and secondary ALL, 28 whereas those of ataxia-telangiectasia gene are specifically associated with T-cell lineage ALL. 29 Likewise, somatic PTPN11 mutations, similar to those present in Noonan syndrome, underlie the risk of lymphoid malignancies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…were related to secondary leukemia. 13,27 Also, the presence of germ line mutations such as those of p53 (Li-Fraumeni syndrome) may underlie the occurrence of primary cancers and secondary ALL, 28 whereas those of ataxia-telangiectasia gene are specifically associated with T-cell lineage ALL. 29 Likewise, somatic PTPN11 mutations, similar to those present in Noonan syndrome, underlie the risk of lymphoid malignancies.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the presence of certain polymorphisms in detoxifying enzymes is associated with increased risk of secondary AML. 12,13 Most previous studies have analyzed all types of secondary malignancies, 14,15 but there are few comprehensive large-scale studies specifically on secondary hematological malignancies. Furthermore, most reports on secondary hematological malignancies focus on second leukemias only.…”
mentioning
confidence: 99%
“…Initial studies on inter-individual variability in risk of tMDS/AML using a candidate gene approach have identified common polymorphisms in low penetrance genes that regulate the availability of active drug metabolite or those responsible for DNA repair. Associations have been observed for glutathione S-transferase genes ( GSTM1 , GSTT1 and GSTP1 ), particularly among those with prior exposure to chemotherapeutic agents that are known GSTP1 substrates, 144 and for P-glycoprotein (encoded by MDR1 ), a cell membrane protein that impacts response to numerous chemotherapeutic agents. 145 A number of studies also have evaluated key DNA repair genes, including mismatch repair family members MLH1 146,147 and MSH2 , 148,149 RAD51 , 150 and XRCC3 .…”
Section: Non-transplant-related Risk Factorsmentioning
confidence: 99%
“…The coding gene of glutathione S-transferase pi-class (GSTP1) is located on chromosome 11q13. GSTP1 polymorphism may affect the function of enzymes and decreased enzyme activity (Allan et al, 2001). Since a broad panel of organs including placenta, prostate, colon, breast, esophagus, brain, spleen and lung express GSTP1 consistently in their tissues (Welfare et al, 1999), and a wide range of precancerous and neoplastic growths have been shown to overexpress GSTP1, which propose a conceivable GSTP1 polymorphism association in breast cancer etiology (Joanne et al, 2000).…”
Section: Introductionmentioning
confidence: 99%